Inclusive Public Policies: access of deaf students to higher education - Leila Santos Mesquita (Universidade Federal do Rio Grande do Sul, 2018)
This paper intends to discuss the enrollment of deaf students in higher education, with focus on the limits and progress of recent public policies of access. A questionnaire was used to interview deaf students from a public high school from the state of Pernambuco, Brazil. The study demonstrates that the non-recognition of sign language as first language and the lack of appropriation of Portuguese language by deaf people are barriers to the access of deaf students to higher education. In face of it, bilingual teaching emerges as a way to increase enrollment.